2022
DOI: 10.1001/jamaoto.2022.2589
|View full text |Cite
|
Sign up to set email alerts
|

Patient With Hearing Loss and a Middle Ear Mass

Abstract: A 65-year-old patient with a history of myocardial infarction, sleep apnea, Meniere disease, and congenital cataract presents with left-sided hearing loss during the past 6 months without evident cause. What is your diagnosis?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Notably, in this case, as well as in most reported cases of tophaceous gout in the middle ear, patients exhibited normal serum uric acid levels. Furthermore, no cases indicated previous gout manifestations in other joints [1][2][3][4].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Notably, in this case, as well as in most reported cases of tophaceous gout in the middle ear, patients exhibited normal serum uric acid levels. Furthermore, no cases indicated previous gout manifestations in other joints [1][2][3][4].…”
Section: Discussionmentioning
confidence: 97%
“…Audiometry serves to quantify the extent of conductive hearing loss. High-resolution computed tomography (HRCT) generally depicts a heterogeneous partially calcified mass within the middle ear, with a distinct radiological appearance as seen in previously reported cases [1][2][3][4]. A semolina-like mass has been used as a descriptive term.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Upon review of previously reported cases of middle ear tophi, none presented with a history of gout, pseudogout, or previous ear surgery (6)(7)(8). Middle ear tophi have been more frequently reported in patients older than 55 years old with the primary clinical manifestation being a simple progressive conductive hearing loss (7).…”
Section: Discussionmentioning
confidence: 99%